Revision of the cold processing phases to obtain a targeted salt reduction in typical Italian dry-cured ham. (March 2020) - Pinna, A.; Saccani, G.; Schivazappa, C.; Simoncini, N.; Virgili, R.
Abstract: The objective of the study was to reduce the salt content of typical Italian dry-cured ham by at least 25%, to meet the "reduced salt" claim. Salt reduction needs process adjustments to maintain product safety and quality in the absence of nitrites. A way was to reduce the salt input and to shorten the salting period compared to the conventional process. The cold drying period of reduced salt (RS) hams was extended, to decrease aw below 0.97 in inner parts and obtain the same safety conditions of control hams (CS). In RS dry-cured hams the salt reduction was accomplished, the generation of biogenic amines was lower than the threshold values generating toxic effects, and color was the same as in the CS ones. However, in RS proteolysis increased, contributing to texture softening. A strengthened salt diffusion from backside rind could contribute to counteract the rise in proteolysis of biceps femoris muscle, depleted of salt during the process of RS hams. Highlights: Reduction of salt in ham was calculated versus an estimated average salt content. Cold processing phases were adapted to obtain hams with 25% reduced salt. Ham weight losses recorded after cold-drying are rough markers of inner aw decrease. Color of end product was unaffected by salt reduction and applied process variations. Process adjustments were unable to counteract proteolysis increase in BF muscle.